2021
DOI: 10.1093/occmed/kqab146
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Silicosis among stone crushing workers in India

Abstract: Background In North India, the mining industry is disorganized and profit-driven. It predisposes its workers towards the development of silicosis. Haryana, a major North Indian state, has developed a compensation–rehabilitation policy for mining workers. Aims This study is the review of the policy’s functioning and limitation from the first 4 years of implementation. Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…A retrospective hospital-based data analysis among patients admitted due respiratory conditions at KCMC from August 2010 to August 2020, revealed the prevalence of silicosis of 14.3% [22], about half of what has been reported from the current study. Studies among other populations have reported a lower prevalence, including that among stone crushers in Haryana, India of around 6.4% [23] and gold miners in South Africa 19.9% [24]. Our selection criteria meant that current study participants were all engaging in drilling of rocks (though in real practice, there is task shifting in which most of the workers will do different work at varying times, including blasting and shovelling of rocks) and given the complete absence of dust reduction mechanisms, including not using water spray during drilling and poorly ventilated mining pits, it could explain this high level of silicosis observed.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective hospital-based data analysis among patients admitted due respiratory conditions at KCMC from August 2010 to August 2020, revealed the prevalence of silicosis of 14.3% [22], about half of what has been reported from the current study. Studies among other populations have reported a lower prevalence, including that among stone crushers in Haryana, India of around 6.4% [23] and gold miners in South Africa 19.9% [24]. Our selection criteria meant that current study participants were all engaging in drilling of rocks (though in real practice, there is task shifting in which most of the workers will do different work at varying times, including blasting and shovelling of rocks) and given the complete absence of dust reduction mechanisms, including not using water spray during drilling and poorly ventilated mining pits, it could explain this high level of silicosis observed.…”
Section: Discussionmentioning
confidence: 99%
“…Another study estimated that approximately 3 million individuals out of 8.5 million construction and building workers in India, are at risk of exposure to silica dust ( 15 ). An observatory study demonstrated that among the 729 silica-exposed individuals in India who underwent medical screening, 465 workers were diagnosed with silicosis with a median age of 45 years ( 16 ). The South African miner association pledged to eliminate silicosis, with the goal of no new cases by 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were also reported by Mukherjee et al (2005) in coal mines using FT-IR spectroscopy. Begum et al (2022) determined that exposure to such hazardous elements in the workplace posed potential threats to the workers including severe lung impairments (Govindagoudar et al, 2022). Studies conducted in granite mines (Singh et al, 2010), zinc mines (Chauhan, 2010), sandstone mines (Nandi et al, 2021) and coal mines (Mishra and Das, 2017) in India also reported that the concentration of such dust was beyond tolerable limit/acceptable standard in the workplace.…”
Section: Introductionmentioning
confidence: 99%